2016
DOI: 10.1089/jamp.2014.1188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mesh Density on Airflow and Particle Deposition in Sinonasal Airway Modeling

Abstract: To ensure numerically accurate simulation results, mesh refinement analyses should be performed for both airflow and particle transport simulations. Tetrahedral-only meshes overpredict particle deposition and are less accurate than hybrid tetrahedral-prism meshes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 30 publications
4
49
0
Order By: Relevance
“…Researchers have explored a myriad of topics, such as characterizing nasal airflow in healthy subjects (Zhao and Jiang, 2014), quantifying nasal filtration of airborne particles (Frank-Ito et al, 2015; Garcia et al, 2015b; Schroeter et al, 2011; Schroeter et al, 2015), heating and humidification of inspired air (Dayal et al, 2016; Goodarzi-Ardakani et al, 2016), the relationship between nasal function and nasal anatomy (Garcia et al, 2016; Patki and Frank-Ito, 2016), and airflow in the paranasal sinuses (Zhu et al, 2012; Zhu et al, 2014). In particular, there is much interest in identifying flow variables that correlate with symptoms of nasal airway obstruction (Garcia et al, 2016; Garcia et al, 2010; Hariri et al, 2015; Kim et al, 2014; Na et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have explored a myriad of topics, such as characterizing nasal airflow in healthy subjects (Zhao and Jiang, 2014), quantifying nasal filtration of airborne particles (Frank-Ito et al, 2015; Garcia et al, 2015b; Schroeter et al, 2011; Schroeter et al, 2015), heating and humidification of inspired air (Dayal et al, 2016; Goodarzi-Ardakani et al, 2016), the relationship between nasal function and nasal anatomy (Garcia et al, 2016; Patki and Frank-Ito, 2016), and airflow in the paranasal sinuses (Zhu et al, 2012; Zhu et al, 2014). In particular, there is much interest in identifying flow variables that correlate with symptoms of nasal airway obstruction (Garcia et al, 2016; Garcia et al, 2010; Hariri et al, 2015; Kim et al, 2014; Na et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Planar nostril and outlet surfaces, as well as the left and right maxillary sinuses regions for tracking particle deposition were constructed. Following the creation of these regions, unstructured tetrahedral meshes were generated with approximately 6 million graded elements; mesh density analysis conducted by Frank-Ito et al (49) found asymptotic behavior for both outlet flow rate and transnasal pressure drop occurred around 4 million cells. This implies that a finer grid of 6 million elements will produce consistent results with those from 4 million unstructured tetrahedral elements.…”
Section: Selection Of Study Cohortmentioning
confidence: 99%
“…This implies that a finer grid of 6 million elements will produce consistent results with those from 4 million unstructured tetrahedral elements. (49) Mesh quality analysis ensured that all tetrahedral elements had an aspect ratio greater than 0.3, to prevent distorted elements from affecting the accuracy of the numerical simulation. A finer three-layer prism-element with a 0.1 mm prism thickness for each layer was created at the sinonasal airway walls to account for near-wall particle trajectories accurately.…”
Section: Selection Of Study Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research in this area considers a steady inlet airflow [25] or an unsteady flow representing inhalation-exhalation cycles [26]. Frank-Ito et al [27] studied the effect of the volume grid cells on the deposition efficiency of the particles while modeling the realistic airflow and particle transport in a realistic human cavity including the paranasal sinuses. They found that by increasing the number of the tetrahedral elements and specially the density of the volume grid cells at the wall, the particle deposition fraction decreased.…”
Section: Introductionmentioning
confidence: 99%